Titanate Tubular Loaded Diatom Fabricated by a Facial Hydrothermal Method for Photocatalytic Enhancement under Visible Light Irradiation - Sang, Nguyen Xuan; Cao Minh, Vo; Phuc, Le Hong; Quynh Trang, Nguyen Thi; Mai, Vo Quang (VNU Journal of Science: Mathematics - Physics; Vol 36 No 4DO - 10.25073/2588-1124/vnumap.4493, 2020)
In this study, homogeneous titanate tubular (TNT) and diatom/TNT composites (D/TNT) were prepared by a facile hydrothermal method. The crystalline structure and morphology of the synthesised samples were studied by X-ray diffractometry (XRD), Raman spectroscopy, Transmission Electron Microscopy (TEM). Furthermore, the photocatalytic activity for degradation of methylene blue (MB) was investigated under sunlight irradiation. The results showed that the MB degradation by D/TNT was higher than bare TNT. Optical properties of the synthesized materials with enhanced photocatalytic activity could be explained through both UV-vis diffuse absorption and photoluminescence emission measurement. These results indicated that there was bandgap narrowing and longer carrier lifetime in the composite sample.